Architecture, Politics and the Sacred in Military Monuments of Fascist Italy - Malone, Hannah (Bloomsbury, 2020)
Benito Mussolini’s Fascist regime in Italy served its political ends through architecture that was at once sacred and modern. This chapter explores that conjunction of religion and modernity through a group of ossuaries (bone depositories), which were built to house the remains of Italian soldiers who fell in the First World War. Whereas, initially, Italians who died fighting in the war were buried in makeshift cemeteries close to the battlefields, in the 1920s and 1930, their remains were disinterred and re-buried by the Fascist regime within large ossuaries. Located along the former front in north-eastern Italy, the Fascist ossuaries are unique among European memorials for their vast scale and monumentality. Innovative in form, they drew on architectural elements of European modernism and Italian Rationalism, as evidenced by a tendency towards abstraction, simplification and reduction of ornament. At the same time, Catholic symbolism was deployed in order to imbue the monuments with sacred power and to serve a political agenda. As secular sites of pilgrimage, the ossuaries fostered veneration of fallen soldiers through imagery that was explicitly religious. They depicted the dead as martyrs and their death as a sacrifice for the redemption of the fatherland. By imposing a narrative that spoke of salvation, they also helped to silence discordant memories of the Great War as pointless slaughter. As well as bolstering support for the Fascist dictatorship, the monuments were meant to prepare the Italian population to fight in future wars. Their combination of religious and political iconography was in the line with the way Fascism acted as a ‘political religion’ or an ideology that adopted religious strategies of propaganda. As the Fascist authorities operated in a deeply Catholic culture, they borrowed tools of persuasion that belonged to the Church. At the same time, they endorsed modern architectural styles as emblematic of the modernity of Fascism. This suggests how, far from disappearing from modern architecture, the sacred was re- invented in new and meaningful ways to serve political functions. The architecture of Fascist Italy contradicts a stereotypical view of modern architecture as a secular movement that is focused on function, technology and rationalism.1 Rather, Mussolini’s regime engendered buildings that were both sacred and modern, or which drew simultaneously on religion and modernism to serve political goals. Italian Rationalism was exceptional among interwar movements in modern architecture in that it was simultaneously 'cosmopolitan and nationalistic, politically progressive and yet fully committed to the political program of Fascism'. As such, it was ideally suited to Fascist ambitions both to modernize Italy and to revive its national traditions – a paradox that also reflected the coexistence of revolutionary and reactionary factions within the regime.2 After the conquest of Ethiopia and the foundation of the Fascist Empire (1936), there was a turn towards traditionalism in ideology, as in architecture. However, the ossuaries emerged from an earlier period in which the Fascist authorities endorsed a range of styles and a unique blend of modernism and tradition. This chapter will show how religious symbolism and modern aesthetics might work together to carry messages of political propaganda. As such, the ossuaries are particularly interesting as they exemplify how religion can be, not only integral to modern aesthetics, but even expressive of modernity. The monuments are ideal spaces for the modern reinvention of the sacred, in part, because of their nature as burial sites. While cemeteries are closely bound to ideas of the sacred, they are also sites for architectural experimentation because of the limited functional requirements of a dead body. To show how modernity and holiness coexisted within the ossuaries, this chapter has three parts: the first looks to the context in which they were built; the second shows why they were built or the aims that they were meant to serve; and the third part focuses on how modern architecture used the sacred to fulfil those aims.
Modern Architecture and the Sacred
PUBLISHED